Expressions of MMP-12, TIMP-4, and Neutrophil Elastase in PBMCs and Exhaled Breath Condensate in Patients with COPD and Their Relationships with Disease Severity and Acute Exacerbations - Wendong Hao; Manxiang Li; Yunqing Zhang; Cailian Zhang; Yani Xue (Journal of Immunology Research)
Objective. The purpose of this study was to compare matrix metalloproteinase-12 (MMP-12), neutrophil elastase (NE), and tissue inhibitor of metalloproteinase-4 (TIMP-4) in peripheral blood of patients with chronic obstructive pulmonary disease (COPD) and controls. At the same time, MMP-12, NE, and TIMP-4 in exhaled breath condensate (EBC) were also evaluated. Methods. Peripheral blood and EBC samples from COPD patients and healthy controls were collected. In serum and EBC, MMP-12, NE, and TIMP-4 proteins were detected by enzyme-linked immunoassays. The mRNA expression levels of MMP-12, NE, and TIMP-4 in peripheral blood mononuclear cells (PBMCs) were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Results. The concentration of TIMP-4 protein in EBC was lower in patients with COPD (P<0.001). MMP-12 (P=0.046), NE (P=0.027), and TIMP-4 (P=0.005) proteins in serum of patients with COPD showed higher levels of concentration. The mRNA of MMP-12 (P=0.0067), NE (P=0.0058), and TIMP-4 (P=0.0006) in PBMCs of COPD patients showed higher expression levels. Compared with stable patients, mRNA expression level of NE (P=0.033) in PBMCs of patients with acute exacerbation of COPD was increased. There were differences in the ratio of MMP-12/TIMP-4 in PBMC (P=0.0055), serum (P=0.0427), and EBC (P=0.0035) samples between COPD patients and healthy controls. The mRNA expression of MMP-12 (r=−0.3958, P=0.0186) and NE (r=−0.3694, P=0.0290) in COPD patients was negatively correlated with pulmonary function. However, the mRNA expression of TIMP-4 (r=0.2871, P=0.0945) in PBMCs was not correlated with the FEV1 of the pulmonary function. Serum MMP-12 level was positively correlated with the MMP-12 level in EBC (P=0.0387). The level of TIMP-4 in serum was not correlated with the level in the EBC sample (P=0.4332). Conclusion. The expression levels of MMP-12, NE, and TIMP-4 in PBMCs and serum were elevated in COPD patients. In PBMCs of COPD patients, the mRNA expression level of NE may predict acute exacerbation, and MMP-12 mRNA expression level may be used to reflect the severity of airflow limitation. However, to better assess their diagnostic or prognostic value, larger studies are necessary.